ETNIS NIAS DI KOTA PADANG TAHUN 1970-2008 : SUATU TINJAUAN SEJARAH SOSIAL BUDAYA - -, Ardiman - (Pendidikan Sejarah, 2014)
This thesis focuses on the social and cultural life of the people ofNias in Padang. Although as ethnic immigrants in the city of Padang, but their presence in  the  community  who  contributed  to Padang as that has opened up areas in the city of Padang. Ethnic Nias in Padang lot to contribute to the progress of the city of Padang, where their presence opens up new areas in the city of Padang. Writing this thesis uses methods of social history, which connects ethnic Nias in Padang Minangkabau  society both from public life and relationships of cultural assimilation among  the  people  of  Nias  culture brought from the region of origin  with  the  community  in Minangkabau  culture. The method  used  in this study include, first stage of gathering resources (Heuristic), Second  stage  of  criticism  Source criticism both  internal  and external  criticism, three  stages of interpretation  in which  this phase commit an understanding of the sources to be studied, and the last stage of Historiography,  is the writing stage of research re<;.;u s. The source used is a source of primary and secondary sources. Writing this thesis uses methods of social history, which connects ethnic Nias in Padang Minangkabau sociely both from public life and relationships of cultural assimilation among the people ofNias culture brought from the region of origin with the community  in  Minangkabau  culture. The method  used  in this  study include, first stage of gathering resources  (Heuristic),  Second  stage of criticism  Source criticism  both  internal and external criticism,  three  stages  of interpretation  in  which  this  phase  commit  an  understanding  of the sources to be studied, and the last stage of Historiography, is the writing stage of research results. The source used s a source of primary  and secondary  sources.